Преступление и наказание: [роман] / Федор Достоевский - Достоевский Федор Михайлович (100 главных книг, 2015)
Экземпляры: ф.13 (20161020) / Инвентарный номер: 53284 / Цена: / Сис.шифр: Р1 / Авт.знак: Д 70 / ГРНТИ: 17.82.31 / ББК: 84 (2Рос-Рус)1